2021
DOI: 10.1186/s13054-021-03457-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, prognostic factors, and outcomes of venous thromboembolism in critically ill patients: data from two prospective cohort studies

Abstract: Background The objective of this study was to describe the prevalence, incidence, prognostic factors, and outcomes of venous thromboembolism in critically ill patients receiving contemporary thrombosis prophylaxis. Methods We conducted a pooled analysis of two prospective cohort studies. The outcomes of interest were in-hospital pulmonary embolism or lower extremity deep vein thrombosis (PE-LDVT), in-hospital nonleg deep vein thrombosis (NLDVT), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
(62 reference statements)
1
9
1
1
Order By: Relevance
“…In the present meta-analysis that encompasses 5296 ICU patients from 21 observational studies, we identified low –to moderate-certainty evidence for the risk factors for VTE, including the COVID-19 severity (i.e., requirement for mechanical ventilation, use of inotropic drugs, length of hospital stay, and SOFA score at VTE screening) and biological parameters (i.e., D-dimer levels, DIC ISTH criteria, CRP level, troponin T, procalcitonin, thrombocytopenia). Some risk factors previously reported were not confirmed by our analysis, including an older age, female sex, obesity [ 36 , 37 ], and a medical history of VTE or cancer [ 38 , 39 ]. Interestingly, the use of anticoagulants at any dose was not associated with a different risk of thrombosis in the univariate analysis.…”
Section: Discussioncontrasting
confidence: 53%
“…In the present meta-analysis that encompasses 5296 ICU patients from 21 observational studies, we identified low –to moderate-certainty evidence for the risk factors for VTE, including the COVID-19 severity (i.e., requirement for mechanical ventilation, use of inotropic drugs, length of hospital stay, and SOFA score at VTE screening) and biological parameters (i.e., D-dimer levels, DIC ISTH criteria, CRP level, troponin T, procalcitonin, thrombocytopenia). Some risk factors previously reported were not confirmed by our analysis, including an older age, female sex, obesity [ 36 , 37 ], and a medical history of VTE or cancer [ 38 , 39 ]. Interestingly, the use of anticoagulants at any dose was not associated with a different risk of thrombosis in the univariate analysis.…”
Section: Discussioncontrasting
confidence: 53%
“…This study found that in our neurointensive care unit patient cohort, the incidence of lower extremity DVT was 36.4%, which was higher than the incidence in patients after neurosurgery who are not admitted to the neurointensive care unit reported by other studies (1,3). This may be because intensive care unit patients have a higher risk of DVT overall (9)(10)(11). Among the 420 patients included in the primary cohort, the age of patients with lower extremity DVT was significantly higher than those without (P < 0.001).…”
Section: Discussionmentioning
confidence: 46%
“…Besides, ICU-AW, DVT, PSs, and VAP are also common complications in CIPs [ 22 24 ]. The reduction of the incidence of these complications can not only improve the QoL and physical function of CIPs but also facilitate their early rehabilitation.…”
Section: Discussionmentioning
confidence: 99%